PERSEPSI GURU SMK JURUSAN BANGUNAN SEKOTA PADANG TENTANG PERLUNYA PENDIDIKAN MITIGASI BENCANA GEMPA DAN TSUNAMI - Noni Aisah Harahap; Revian Bodi; Fitra Rifwan; Juniman Silalahi (CIVED, 2018)
Abstract— The aim of the research is to find out the perception of vocational school’s teachers specialized in Building  in Padang city the need for education of mitigation of earthquake and tsunami. The type of this research was descriptive quantitative. The population of this research were 46 teachers of Vocational School in Padang. The technique of sample collecting was simple random sampling technique, so that about 41 teacher were selected. The data of this research were obtained through questionnaire and then analyzed by using descriptive analysis. Based on the results it can be concluded that the vocational school teachers’ perception specialized about building subject in padang about the need of disaster mitigation education was in sufficient category. It can be seen based on the indicator that are 1) socialization about knowledge and attitude to ward disaster was catagorized as sufficient with degree achievement of 78.48%, 2) the equipping of school policies or programs about disaster preparedness was catagorized as sufficient with degree of achievement of 76.98%, 3) providing the school action plan for dealing with disaster was catagorized as high with achievement degree of 81.02%, and 4) school community training in emergency disaster emergency procedures was catagorized as high with achievement degree of 80.89%.                                                                                                      Key Word: Keywords: Perception, Disaster Mitigation Education